Предмет: Математика,
автор: MilenaMilo
Решить уравнение 76-x=37 x+65=92. (X+37)-49=18
Ответы
Автор ответа:
0
76-x=37
X=76-37
X=39
X+65=92
X=92-65
X=27
(X+37)-49=18
X+37=18+49
X+37=67
X=67-37
X=30
X=76-37
X=39
X+65=92
X=92-65
X=27
(X+37)-49=18
X+37=18+49
X+37=67
X=67-37
X=30
Автор ответа:
0
1) 76 - х = 37 2) х + 65 = 92 3) (х+37) - 49 = 18
-х = 37-76 х = 92 - 65 х+ 37 - 49 = 18
-х = -39 х= 27 х = 18 -37 +49
х = 39 х = 30
-х = 37-76 х = 92 - 65 х+ 37 - 49 = 18
-х = -39 х= 27 х = 18 -37 +49
х = 39 х = 30
Автор ответа:
0
сошлось:)
Автор ответа:
0
хах
Похожие вопросы
Предмет: Математика,
автор: roza6767
Предмет: Русский язык,
автор: vikasobakasergacheva
Предмет: Биология,
автор: pitachokrahat
Предмет: География,
автор: Vicky12
Предмет: Математика,
автор: katyaalekseeva1